Doppler-shifted inertial oscillations on a beta plane - Zhai, X; Greatbatch, R; Sheng, J (2005)
On the spherical earth, and in the absence of a background flow, the poleward propagation of near-inertial oscillations is restricted by the turning latitude. A background flow, on the other hand, provides a way to increase the apparent frequency of near-inertial waves through Doppler shifting. In this note, it is shown that near-inertial oscillations can be advected to latitudes higher than their turning latitude. Associated with the poleward advection there is a squeezing of the meridional wavelength. A numerical model is used to verify this result. The squeezed inertial oscillations are vulnerable to nonlinear interactions, which could eventually lead to small-scale dissipation and mixing. © 2005 American Meteorological Society.